Hubungan Tingkat Stres Dengan Kualitas Tidur Lansia Di Wilayah Kerja Puskesmas Prumnas Lubuklinggau Tahun 2025 - Soska Dwi Putra; Darmawansyah Darmawansyah; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
In Indonesia, approximately 40% to 50% of the population experiences sleep disorders, most of whom are elderly. These sleep disorders usually occur simultaneously with other conditions such as physical problems and mental illnesses (depression, anxiety disorders) that can lead to poor sleep quality (Khadijah, 2023). The objective of this study is to determine the relationship between stress levels and sleep quality among the elderly in the Prumnas Lubuklinggau Community Health Centre Working Area in 2025.The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 62 people.The results of the univariate test analysis showed that a small proportion of respondents (22.6%) had severe stress, while the majority of respondents (51.6%) had poor sleep quality. The results of the bivariate analysis of the relationship between stress levels and sleep quality in the elderly (p-value 0.002) showed that there is a relationship between stress levels and sleep quality in the elderly in the Prumnas Lubuklinggau Community Health Centre Working Area in 2025.The elderly are advised to manage stress by doing relaxation activities such as light exercise, praying, and increasing positive social interactions. Regulating a regular sleep routine, avoiding caffeine consumption at night, and creating a comfortable sleeping environment can also help improve sleep quality, as well as understanding the relationship between stress levels and sleep quality in the elderly in their area. For the research site, this can be used as additional information about the relationship between stress levels and sleep quality in the elderly. For the Faculty of Health Sciences at Dehasen, this can be used as input in planning and developing health intervention programmes to address existing issues related to the relationship between stress levels and sleep quality in the elderly.